2023
DOI: 10.1523/eneuro.0452-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Water-Reaching Platform for Longitudinal Assessment of Cortical Activity and Fine Motor Coordination Defects in a Huntington Disease Mouse Model

Abstract: Huntington disease (HD), caused by dominantly inherited expansions of a CAG repeat results in characteristic motor dysfunction. Although gross motor defects have been extensively characterized in multiple HD mouse models using tasks such as rotarod and beam walking, less is known about forelimb deficits. We develop a high-throughput alternating reward/nonreward water-reaching task and training protocol conducted daily over approximately two months to simultaneously monitor forelimb impairment and mesoscale cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Moreover, only at this age, decreased pericyte count was present in the S1Ctx and a trend of decrease in the CPu at this age. It can be inferred that loss of pericytes in these regions can be a transitory change, coinciding with the phenotypic conversion in this model, that is being compensated for after initial abnormalities occur 26,58 . Interestingly, these regions show consistent hyper(de)activations in QPPs.…”
Section: Mhtt Deposition In Astrocytes and Pericytes Linked To Qpp Al...mentioning
confidence: 57%
See 2 more Smart Citations
“…Moreover, only at this age, decreased pericyte count was present in the S1Ctx and a trend of decrease in the CPu at this age. It can be inferred that loss of pericytes in these regions can be a transitory change, coinciding with the phenotypic conversion in this model, that is being compensated for after initial abnormalities occur 26,58 . Interestingly, these regions show consistent hyper(de)activations in QPPs.…”
Section: Mhtt Deposition In Astrocytes and Pericytes Linked To Qpp Al...mentioning
confidence: 57%
“…Remarkably, the RspCtx also showed a premature peak of either activation or deactivation in both long QPPs, indicating that there is an asynchronous peak in the BOLD activity that leads to altered time-locked relationships with other regions. A recent study in zQ175DN mice of the same age reported altered mesoscale cortical activity in the RspCtx during a behavioral task where they report that initial behavioral deficits occur at this age, suggesting a potential role of the RspCtx in phenoconversion in this model 58 . The overall diminished DMLN activity at 10 months also led to a breakdown of the LCN DMLN state flux reflected in the lack of presence of the LCN DMLN QPP in the zQ175DN HET group, alongside the decreased occurrence of DMLN.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Here, through an unbiased areal screen with PN type resolution, we have identified a dynamic cortical network that correlates with the sequential forelimb and orofacial movements that compose RGD. Compared with most previous wide-field imaging studies in the mouse 39,40,7679 , two design features of our study enabled mapping this network. First, the 4 driver lines that target major PN types, in addition to the pan-PN Emx1 line, allowed us to resolve PN-characteristic areal activity patterns that were masked in the broad population signal.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used wide-field calcium or voltage imaging to study mesoscale dynamics in mouse models for Huntington disease (HD 88 , 89 ). Sepers et al.…”
Section: Wide-field Imaging Of the Disordered Brainmentioning
confidence: 99%